2014
DOI: 10.1107/s1399004714023827
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of human mitochondrial 3-ketoacyl-CoA thiolase (T1): insight into the reaction mechanism of its thiolase and thioesterase activities

Abstract: Crystal structures of human mitochondrial 3-ketoacyl-CoA thiolase (hT1) in the apo form and in complex with CoA have been determined at 2.0 Å resolution. The structures confirm the tetrameric quaternary structure of this degradative thiolase. The active site is surprisingly similar to the active site of the Zoogloea ramigera biosynthetic tetrameric thiolase (PDB entries 1dm3 and 1m1o) and different from the active site of the peroxisomal dimeric degradative thiolase (PDB entries 1afw and 2iik). A cavity analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…Only the mutation of Cys458 to Ser impaired glucose deprivation-induced TPb oxidation ( Figure 5C), suggesting that Cys458, conserved across several species ( Figure S5C), is the major site of oxidation in TPb. A structural analysis of thiolase family members suggested that Cys458 may be essential for the enzymatic activity of thiolase, during which it provides a proton to acetyl-CoA and then removes a proton from the incoming CoA (Haapalainen et al, 2006;Kiema et al, 2014). Mutating Cys458 suppressed the KACT activity of TPb not only in vitro but also in cells under normal conditions ( Figure 5D; Figures S5D and S5E), confirming the requirement of this cysteine for the enzymatic activity of TPb.…”
Section: Nur77 Interaction With Tpb In Mitochondria Facilitates Cell mentioning
confidence: 57%
“…Only the mutation of Cys458 to Ser impaired glucose deprivation-induced TPb oxidation ( Figure 5C), suggesting that Cys458, conserved across several species ( Figure S5C), is the major site of oxidation in TPb. A structural analysis of thiolase family members suggested that Cys458 may be essential for the enzymatic activity of thiolase, during which it provides a proton to acetyl-CoA and then removes a proton from the incoming CoA (Haapalainen et al, 2006;Kiema et al, 2014). Mutating Cys458 suppressed the KACT activity of TPb not only in vitro but also in cells under normal conditions ( Figure 5D; Figures S5D and S5E), confirming the requirement of this cysteine for the enzymatic activity of TPb.…”
Section: Nur77 Interaction With Tpb In Mitochondria Facilitates Cell mentioning
confidence: 57%
“…Moreover, it was reported by others that enzymatically active thiolase is a dimer or tetramer (24). Thus, p46Shc can directly bind to ACAA2 in mitochondria with K D ϭ 54.62 Ϯ 34.87 nM (Fig.…”
Section: P46shc Is the Only Mitochondrial Shc Isoform Under Physiologmentioning
confidence: 82%
“…The N ‐ and C ‐terminal residues are far away from the catalytic site, being on the opposite site of the subunit. The built model of each subunit has the distinct conserved thiolase superfamily fold that can be subdivided into the N ‐terminal domain, loop domain, and C ‐terminal domain (Haapalainen et al, ; Kiema et al, , ). The N ‐ and C ‐terminal domains have the same βαβαβαββ‐topology and these two domains jointly form a five‐layered α‐β‐α‐β‐α structure.…”
Section: Structural Features Of the T2 Thiolasementioning
confidence: 99%